Рогачицька та рєпінська культури в колі культур пізнього енеоліту — ранньої бронзи Східної Європи - Спіцина, Л.А. (Археологія, 2017)
Розглядається походження та хронологічні межі двох культурних явищ доби пізнього енеоліту—ранньої бронзи Східної Європи. Analysis of the available source base makes it possible to determine the area of distribution, to trace the formation, and to outline the timeframe of Rohachyk and Riepin cultures. Rohachyk culture formed at a local ground (Nyzhniomykhailivka group of monuments and Dereivka culture) by the powerful influence of Late Trypillia culture. Some features of the material culture of Rohachyk traditions’ bearers evidence their contacts with the populations of the Crimea, Riepin culture, Late Maikop culture, as well as of more distant cultures, namely, Globular Amphora and Baden ones. Investigation of possible components forming Riepin culture identified the Siverskyi Donets River region as the most likely area for this process. Actually, it is here where cultures which traditions, to the author’s opinion, had a decisive influence on the process of the Riepin culture’s creation, were widely represented; they are Dereivka and Pit-Comb Ware cultures. In addition, the Riepin culture population borrowed some features from its’ neighbours. Trypillia and Rohachyk cultures populations are first among the latter. Some elements of the decoration on dishes evidence for contacts between Riepin and Globular Amphora cultures populations. Consequently, two phenomena, Rohachyk and Riepin cultures, are prominent among Eastern European antiquities in the Late Chalcolithic and the Early Bronze Age. Rohachyk culture sites are known in the area between the Dnipro and Buh Rivers, in the Dnipro River right bank lower region, and in the Crimea. The bearers of the Riepin culture traditions occupied left bank of the Dnipro: Siverskyi Donets River region, the northwest area of the Sea of Azov, and further to the east. Анализ имеющейся базы источников позволяет обозначить ареалы, проследить формирование, определить временные рамки рогачикской и репинской культур. Формирование рогачикской культуры происходило на местной основе (нижнемихайловская группа памятников и дереивская культура) при мощном воздействии со стороны позднетрипольского мира. Отдельные черты материальной культуры носителей рогачикских традиций свидетельствуют о контактах с жителями Крыма, репинцами, позднемайкопским населением, и более отдаленными культурами — Баден и шаровидных амфор. Исследование возможных составляющих формирования репинской культуры определяет регион Северского Донца как наиболее вероятный ареал этого процесса. Собственно, именно здесь широко представлены культуры, традиции которых, на наш взгляд, имели решающее влияние на процесс формирования репинской культуры — дереивская и культура ямочно-гребенчатой керамики. Кроме этого, некоторые черты были заимствованы репинским населением у соседей. Среди них, в первую очередь, речь идет о трипольском и рогачицком. Отдельные элементы оформления посуды указывают на контакты репинцев с культурой шаровидных амфор. Таким образом, среди древностей позднего энеолита—ранней бронзы Восточной Европы хорошо выделяются два явления — рогачицкая и репинская культуры. Памятники рогачицкий культуры известны в Днепровско-Бугском междуречье, на Правобережье Нижнего Днепра и в Крыму. Носители репинского традиций занимали пространства к востоку от Днепра—Северско-Донецкий регион, Северо-Западное Приазовье и дальше на восток.